Effects of low- and high-intensity exercise on emotional face processing: an fMRI face-matching study. Issue 6 (21st June 2019) - Schmitt, Angelika; Martin, Jason Anthony; Rojas, Sandra; Vafa, Ramin; Scheef, Lukas; Strüder, Heiko Klaus; Boecker, Henning
Abstract: Physical exercise has positive effects on mood and it reduces clinical depression and states of anxiety. While previous work mostly used subjective measures to study the effect of exercise upon emotions, this study for the first time employed blood oxygen level dependent functional magnetic resonance imaging (fMRI) to unravel associated neuronal changes of the emotional face-processing network in response to acute exercise. A total of 25 male athletes underwent fitness assessments to define two standardized 30 min exercise interventions (low and high intensity). The Positive and Negative Affect Schedule (PANAS) was completed pre- and post-exercise and neuronal responses to neutral, happy and fearful facial expressions were determined using an fMRI-based face-matching paradigm. Complete data sets were acquired in 21 participants (mean age, 27.2 ± 4.2 years). Both exercise interventions induced significant increases of the PANAS positive affect scale. Modulations of brain activation patterns following acute exercise were found only for fearful facial stimuli vs forms: reduced brain activation in posterior cingulate cortex/precuneus for the low condition and reduced activity in caudate nucleus and ventral anterior putamen for the high condition. In conclusion, this study provides first in vivo evidence that acute strenuous exercise interferes with emotional face-processing brain regions in an emotion type-specific manner.